2020
DOI: 10.1186/s12931-020-01391-3
|View full text |Cite
|
Sign up to set email alerts
|

Suppressed nuclear factor-kappa B alleviates lipopolysaccharide-induced acute lung injury through downregulation of CXCR4 mediated by microRNA-194

Abstract: Acute lung injury (ALI) is a highly lethal pulmonary disease that causes edema, hypoxemia and respiratory failure. Recent evidence indicates that nuclear factor-kappa B (NF-κB) plays a crucial role in ALI development. However, the regulatory mechanism of NF-κB on ALI remains enigmatic. In this study, we investigated potential molecular mechanism of NF-κB on ALI induced by lipopolysaccharide (LPS). BALB/c mice were subjected to intratracheal spraying of LPS to generate an ALI mode, with the activity of NF-κB in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
3
11
0
Order By: Relevance
“…The results of inflammatory factor assay showed that supplementation with EcN-MT reduced the transcriptional levels of IL-1β, IL-6 and TNF-α inflammatory factors (Figure 3). In addition, according to the report (Chen et al, 2020), PDTC is the most commonly used inhibitor of NF-κB. Inhibition of NF-κB activation with PDTC also reduced inflammation, oxidative stress in the liver (Figure 5).…”
Section: Discussionmentioning
confidence: 89%
“…The results of inflammatory factor assay showed that supplementation with EcN-MT reduced the transcriptional levels of IL-1β, IL-6 and TNF-α inflammatory factors (Figure 3). In addition, according to the report (Chen et al, 2020), PDTC is the most commonly used inhibitor of NF-κB. Inhibition of NF-κB activation with PDTC also reduced inflammation, oxidative stress in the liver (Figure 5).…”
Section: Discussionmentioning
confidence: 89%
“…The NF-κB family controls various processes such as immunity and inflammation 36 . Chen et al 37 confirmed that NF-κB signaling pathway was abnormally activated in the AT-II of patients with ALI and promoted the production of inflammatory factors including IL-1β, IL-6 and TNF-α, which initiated the inflammatory cascade. Besides, necroptosis might be involved in endothelial injury 38 and adherens junction were critical for basal pulmonary microvascular integrity 39 .…”
Section: Discussionmentioning
confidence: 96%
“…The NF-kB signaling pathway has an irreplaceable role in regulating excessive inflammatory damage and response (51,52). When the NF-kB signaling pathway is engaged, inflammatory factors like TNF-a, IL-6, and IL-1b are generated during ALI (53,54). TAK1 is a required kinase for TLR4-mediated NF-kB activation (32).…”
Section: Discussionmentioning
confidence: 99%